Value of urinary microalbumin test in cancer patients with borderline serum creatinine level - Das, Sawmik; Sarma, Anupam; Sharma, Jagannath Dev; Ahmed, Shiraj; Krishnatreya, Manigreeva; Kataki, Amal Chandra (International Journal of Research in Medical Sciences, 2017)
Background: Micralbuminuria (MA) is an early sign of incipient renal damage and cancer patients are at the risk of developing kidney diseases due to the use of nephrtoxic chemotherapeutic agents. Methods: A pilot study of urinary microalbumin on 41 patients with borderline serum creatinine was carried out at regional cancer centre of North-East India during the period from June to August 2014. The patients whose serum creatinine levels were between 1.2 mg/dl to 1.3 mg/dl were considered as borderline for the present study. The assays were performed with a dimension Rxl max random access biochemistry analyzer. Results: Out of 41 cases, 22 (53.6%) had MA, M:F = 1.75, <45 years 3 (13.6%) patients, in 45 years - 65 years 17 (77.2%) patients, and >65 years 2 (9.0%) patients were detected with urinary microalbumin. Chi square test showed P = 0.695 (Fisher’s exact P value). Conclusion: Testing of urinary microalbumin can be done in cancer patients with borderline serum creatinine level in order to identify patients at risk of developing kidney disease.